Navigating English learning in the digital era: Millennial students’ strategies at a private university in Yogyakarta - Hatmanto, Endro Dwi; Pratolo, Bambang Widi; Nafi’ah, Aisyah Umi; Alsulami, Naif Daifullah; Gendroyono , Gendroyono (Teaching English as a Foreign Language Journal, 2025)
This study investigates the learning strategies of millennial students and the role of digital technologies in English language learning at a private university in Yogyakarta. Using a qualitative descriptive design, five participants were selected using purposive sampling, interviewed, and data were analyzed thematically. The findings reveal six dominant strategies: bite-sized learning, autonomous learning, collaborative learning, game-based learning, mobile learning, and multimodal learning. Digital tools—such as ChatGPT, Google Scholar, YouTube, Duolingo, and Zoom—were found to support flexible, engaging, and self-paced learning environments. These practices align with constructivist and adaptive learning theories, highlighting learner autonomy, feedback, and diverse media use. While digital platforms promote active and personalized learning, the study also notes challenges related to information literacy, self-regulation, and access equity. This research offers insights into how technology enhances ELT practices and provides practical implications for educators aiming to develop inclusive and future-ready English learning environments.